Sex Offending and Situational Motivation: Findings From a Qualitative Analysis of Desistance From Sexual Offending. (November 2016) - Farmer, Mark; McAlinden, Anne-Marie; Maruna, Shadd
Sex offending is typically understood from a pathology perspective with the origin of the behavior thought to be within the offending individual. Such a perspective may not be beneficial for those seeking to desist from sexual offending and reintegrate into mainstream society. A thematic analysis of 32 self-narratives of men convicted of sexual offences against children suggests that such individuals typically explain their pasts utilizing a script consistent with routine activity theory, emphasizing the role of circumstantial changes in both the onset of and desistance from sexual offending. It is argued that the self-framing of serious offending in this way might be understood as a form of "shame management, " a protective cognition that enables desistance by shielding individuals from internalizing stigma for past violence.